2012
DOI: 10.1063/1.4768292
|View full text |Cite
|
Sign up to set email alerts
|

Designer Ge quantum dots on Si: A heterostructure configuration with enhanced optoelectronic performance

Abstract: An otherwise random, self-assembly of Ge quantum dots (QDs) on Si has been controlled by nano-patterning and oxidation to produce QDs with desired sizes, locations, and depths of penetration into the Si substrate. A heterostructure consisting of a thin amorphous interfacial oxide between the Ge QD and the Si substrate is shown to improve crystalline quality by de-coupling the lattice-matching constraint. A low dark current density of 1.1 lA/cm 2 and a high photocurrent enhancement up to 35 000 and 1500, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(58 citation statements)
references
References 29 publications
4
54
0
Order By: Relevance
“…Considering the work functions for Al (4.16 eV), NiGe (5.2 eV), Ge (4.33 eV), and SiGe (4.55 eV) and the gate oxide thickness of 3-4 nm, our experimental observations of negative Vfb suggest estimated positive fixed charge densities of ~5 × 10 11 cm −2 at interfaces of SiO2/SiGe and SiO2/Ge dot. It is interesting to note that the positive fixed charges measured for our NiGe/SiO2/SiGe and Al/SiO2/Ge-dot/SiO2/SiGe MOS capacitors are in contrast to the conventional expectation of negative fixed charges produced by the thermal oxidation of SiGe alloys (LeGoues et al, 1989;Nayak et al, 1990Nayak et al, , 1992 or at high-k dielectric/Ge interfaces generated either by chemical vapor deposition or atomic layer deposition (Bai et al, 2005;Zhang et al, 2006;Deng et al, 2011) As described in our previous reports (Kuo et al, 2012;Lai et al, 2015), the interfacial SiO2 layer between the Ge dot and the SiGe shell is formed by the thermal oxidation of Si interstitials that are released from the Si substrate. The oxide layer between the Ge dot and the deposited Al gate is formed by the thermal oxidation of Si interstitials that migrate along the surface of Ge dot to its distal end.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Considering the work functions for Al (4.16 eV), NiGe (5.2 eV), Ge (4.33 eV), and SiGe (4.55 eV) and the gate oxide thickness of 3-4 nm, our experimental observations of negative Vfb suggest estimated positive fixed charge densities of ~5 × 10 11 cm −2 at interfaces of SiO2/SiGe and SiO2/Ge dot. It is interesting to note that the positive fixed charges measured for our NiGe/SiO2/SiGe and Al/SiO2/Ge-dot/SiO2/SiGe MOS capacitors are in contrast to the conventional expectation of negative fixed charges produced by the thermal oxidation of SiGe alloys (LeGoues et al, 1989;Nayak et al, 1990Nayak et al, , 1992 or at high-k dielectric/Ge interfaces generated either by chemical vapor deposition or atomic layer deposition (Bai et al, 2005;Zhang et al, 2006;Deng et al, 2011) As described in our previous reports (Kuo et al, 2012;Lai et al, 2015), the interfacial SiO2 layer between the Ge dot and the SiGe shell is formed by the thermal oxidation of Si interstitials that are released from the Si substrate. The oxide layer between the Ge dot and the deposited Al gate is formed by the thermal oxidation of Si interstitials that migrate along the surface of Ge dot to its distal end.…”
Section: Discussionmentioning
confidence: 67%
“…Our previous results (Chien et al, 2011;Kuo et al, 2012;Wang et al, 2013;Chen et al, 2014;Lai et al, 2015) have shown that thermal oxidation performed on poly-Si0.85Ge0.15 nano-pillar structures preferentially converts the Si from the poly-Si0.85Ge0.15 to SiO2, leading to the formation of a single Ge dot within each oxidized nano-pillar through an unusual Ostwald Ripening process consolidating the segregated Ge nanocrystallites (Chien et al, 2011). Interestingly, excess thermal oxidation (or thermal annealing) of 15-65 min enables the as-formed Ge dot to penetrate the underlying, buffer Si3N4 layer, and ultimately form a 2-15-nm-thick Si1−xGex-shell layer (x > 0.5) with a "cup"-shape morphology near the top surface of the Si substrate when the Ge dot comes in close proximity to the Si substrate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The SiGe pillar density is approximately 1 × 10 9  cm −2 over the buffer Si 3 N 4 layers. Next, the nanopatterned structure is subjected to thermal oxidation at 900 °C within an H 2 O ambient producing 90-nm diameter, spherical Ge QDs that migrate into the buffer Si 3 N 4 layer [17, 18], as shown in Fig. 1a.…”
Section: Methodsmentioning
confidence: 99%